Inhibition of S-Phase Cyclin-Dependent Kinase Activity Blocks Expression of Epstein-Barr Virus Immediate-Early and Early Genes, Preventing Viral Lytic Replication - Kudoh, Ayumi (American Society for Microbiology, 2004)
The induction of lytic replication of the Epstein-Barr virus (EBV) completely arrests cell cycle progression, in spite of elevation of S-phase cyclin-dependent kinase (CDK) activity, thereby causing accumulation of hyperphosphorylated forms of retinoblastoma (Rb) protein (A. Kudoh, M. Fujita, T. Kiyono, K. Kuzushima, Y. Sugaya, S. Izuta, Y. Nishiyama, and T. Tsurumi, J. Virol. 77:851-861, 2003). Thus, the EBV lytic program appears to promote specific cell cycle-associated activity involved in the progression from G(1) to S phase. We have proposed that this provides a cellular environment that is advantageous for EBV productive infection. Purvalanol A and roscovitine, inhibitors of S-phase CDKs, blocked the viral lytic replication when cells were treated at the early stage of lytic infection, while well-characterized inhibitors of enzymes, such as mitogen-activated protein kinase, phosphatidylinositol 3-kinase, and protein kinase C, known to be involved in BZLF1 gene expression did not. Inhibition of CDK activity resulted in the accumulation of the hypophosphorylated form of Rb protein and inhibition of expression of EBV immediate-early and early proteins. Cycloheximide block-and-release experiments clearly demonstrated that even in the presence of enough amounts of the BZLF1 protein, purvalanol A blocked expression of lytic viral proteins at transcription level. Furthermore, reporter gene experiments confirmed that BZLF1-induced activation of early EBV promoters was impaired in the presence of the CDK inhibitor. We conclude here that the EBV lytic program promotes specific cell cycle-associated activity involved in the progression from G(1) to S phase because the S-phase-like cellular environment is essential for the expression of immediate-early and early genes supplying the viral replication proteins and hence for lytic viral replication.